Predicting endotracheal tube size from length: Evaluation of the Broselow tape in Indian children - Shalini Subramanian; Madhavi Nishtala; Chandrika Yabagodu Ramavakoda; Gaurang Kothari (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Several formulae are available to estimate endotracheal tube (ETT) size in children. This study was designed to compare the ETT estimated by the Broselow tape (BT) with age-based estimation of ETT size and to identify the most accurate formula for the prediction of uncuffed ETT size in Indian children. Material and Methods: Pediatric patients aged 1 month-6.5 years undergoing emergency or elective surgery under general anesthesia requiring endotracheal intubation with uncuffed ETT were included in this study. The ETT size was selected based on the age formula (Penlington formula). The ETT used was deemed to be of correct fit based on the delivery of adequate tidal volume and presence of minimal leak at 20 cm H2O. The actual ETT used was compared with that predicted by age, length of the child, BT, and fifth fingernail width of the child using Pearson's correlation. Results: In children aged <6 months, the ETT used was found to correlate with length (r = 0.286, P = 0.044) and finger nail width (r = 0.542, P< 0.001) of the children. In children >6 months, the ETT used correlated with that predicted from age, BT, length, and fingernail width of the children. In our study, BT has an overall correct predictability rate of 50.3% whereas the age-based formula has a correct prediction rate of 59.8% and length-based formula is 48.7% accurate. Conclusion: Length of the child has a good correlation with size of the ETT to be used in Indian children across all age groups. BT is an effective tool to predict ETT size in children >6 months.